STUDI IMPLEMENTASI TRANSISI KURIKULUM NASIONAL DAN INTEGRASI KEBIJAKAN GLOBAL–LOKAL DI SEKOLAH DASAR - Reski Permata Sari Jamaluddin; Suardi (STKIP Subang, 2025)
This study aims to examine the implementation of the national curriculum transition and the integration of global–local policies in primary schools. The research was conducted at SD As’Adiyah 4 Baru Impa-Impa using a qualitative descriptive approach. Data were collected through interviews, classroom observations, document analysis, and focus group discussions involving the school principal, lower-grade and upper-grade teachers, students, and parents. The findings show that the transition from the 2013 Curriculum to the Merdeka Curriculum has been implemented gradually through socialization, internal training, and adaptation of teaching devices. Project-based learning, particularly the Pancasila Student Profile Project (P5), has been applied and encourages student engagement, although teachers still face challenges related to collaboration, time management, and limited facilities. The integration of local content and digital literacy has begun, but remains at a basic level. Strengthening teacher capacity, stakeholder involvement, and school support systems is essential to ensure effective curriculum implementation and sustainable learning quality.